ANALISIS ISI FOTO JURNALISTIK PADA KOLOM CITIZEN SHOOTHARIAN TRIBUN PEKANBARU - Vio Payoka; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Citizen Journalism phenomenon began to spread to the people of Riau.Tribune Pekanbaru as a battering ram to local media that provide a space for people to write down related to the problems they face, named Rubric Citizen Shoot.The section contained in pages 32 and there is a column provided for additional photos sent by residents and is published every Monday to Saturday.Through the column free citizens send news photos about any issues or incidents that they face, but there are still many shortcomings in the photos sent by residents in the column of the Citizen Shoot.Therefore, this study aimed to analyze the content of photos in a coldumn using the method EDFAT citizen Shoot in the Daily Tribune Pekanbaru.Descriptive qualitative in-depth interviews.This study is also using the model of agenda setting that emphasizes Tribune Pekanbaru provides a column Citizen Shoot with a view to involving the community as a supervisor in any problems that occur.The research was conducted on a column Citizen Shoot, published December 24, 2015 until January 2, 2016 and to determine the theme of ceremonial photograph.This research subject collect the images published on December 24, 2015 until January 2, 2016, for additional investigators interviewed the result of the photo editor column Tribune Pekanbaru citizen Shoot and professor of photojournalism UIN SUSKAThe results of this study is the first to rely on the fact something that is seen, the two never do interviews, the third no screening process photos posted by people who do ignore the rules in news photos, fourth understanding of the citizens will be news photos still is lacking.Meanwhile, the photo elements found some results of the research that has been done, the first photos sent by citizens still included in the category of factual, the second photograph sent by citizens still displays a number of elements jurnalisitik should be in the photo, third residents and editors still pay attention to the importance of a phenomenon to be newsworthy, the four photos made news by residents are still included in the category of ceremonial.Keywords: Photo Analysis, Journalism, Citizen Journalism, Tribun Pekanbaru.